Molecular mechanism of barnacle adhesion : a structural approach and underlying biochemistry - Hur, SunYoung (Nanyang Technological University, 2023)
Barnacles adhere themselves robustly and permanently to diverse underwater substrates through strong interactions of a multi-protein complex layer called the “cement”. However, the intermolecular interactions responsible for the strong adhesive properties of the barnacle cement remains poorly understood. A central hypothesis of this thesis is that underwater properties of the cement complex are intimately linked to the molecular characteristics of cement proteins (CPs) forming the cement complex.